Charles Austin Beard's Economic Interpretation of the American Century through His Journalistic Writings. Issue 1 (2nd January 2023) - Drake, Richard
ABSTRACT: Beginning with the publication of An Economic Interpretation of the Constitution of the United States in 1913, Charles Austin Beard gained fame and notoriety as a historian by writing about the power of money over politics and policy. In his analysis of American history, he did not make an exception for the Second World War or the Cold War. Those conflicts, too, had an economic subtext. Yet, in his two most famous books dealing with the dawn of the American Century, American Foreign Policy in the Making, 1932–1940: A Study in Responsibilities (1946) and President Roosevelt and the Coming of the War, 1941: A Study in Appearances and Realities (1948), he focused narrowly on Roosevelt's foreign policy decisions. These books contributed to the impression that in his later years he had moved beyond the economic interpretation of history. A leading public intellectual, Beard also wrote numerous magazine articles about the motives behind America's interwar, wartime, and post-war foreign policy. His journalistic first draft of history crucially supplements the last books that he published and shows him to have retained the view that there is no politics without economics.